Guinea-Bissau : Poverty Reduction Strategy Paper; Joint Staff Advisory Note. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This Joint Staff Advisory Note reviews the first full Poverty Reduction Strategy Paper (PRSP) prepared by the government of Guinea-Bissau. The PRSP was prepared within a participatory process, and builds on grassroots consultations at the national level that involved all segments of society. The PRSP highlights broad areas of intervention for each strategic pillar but lacks a clear prioritization of activities and programs. IMF staff agrees with the PRSP's emphasis that high unemployment rates and heavy reliance on agriculture as the main source of employment are major concerns for poverty reduction.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet